Novel multidimensional fractionation techniques for the compositional analysis of impact polypropylene copolymers - Cheruthazhekatt, Sadiqali (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.